Plan de marketing turístico para el bosque protector Sayo de la parroquia rural Santiago, Cantón Loja, Provincia de Loja 2014 - Betancourt Gordillo, Maritza Valeria (2016)
In the south of the Ecuador the county of Loja is located, of the canton Loja, Santiago, is one of the rural parishes of this canton, inside what is the county of Loja fifteen protective forests they exist of which two of them are in the Parish Santiago, in spite of the importance that you/they represent it is ignored by the population so much local as foreigner. The problem is centered in the promotion lack and tourist diffusion that it exists in Santiago's parish for the Protective Forest Sayo, this is attributed to the lack of the actors' support related in the sector that has not allowed to take advantage of tourist the potential resources with those that counts the parish, due to reasons extended the necessity precedently it was seen of outlining a "Plan of tourist marketing of the rural parish Santiago of the canton Loja, county of Loja 2014" The objective of this investigation is to promote and to diffuse the attractiveness through the elaboration of a Plan of Tourist Marketing, of the same one that you/they are derived the specific ones as to carry out a diagnosis of the current situation and to propose a plan of tourist marketing for the protective forest Sayo, for its execution methods were used that they optimize the realization of the thesis work like they are: scientific, analytic synthetic, bibliographical, descriptive and technical as the observation, he/she interviews, it interviews, the sample, and through field exits that contributed to the execution of the objectives. For the realization of the diagnosis of the protective forest Sayo was carried out an analysis of the macro-environment where the demographic, economic factor, sociocultural, political and technological factor, was analyzed of the parish Santiago, he/she was also carried out an analysis of the micro-environment for it was used it an interview to the Mr. Happy 6 Ahuaca vice-president of Santiago's GAD that spontaneously offered information on the place it was also investigated on the technical records of the attractiveness that exist inside the forest like reference for the development of the investigation, the same ones that we find them in Santiago's GAD like contribution of Miss Nataly Jaramillo in its denominated thesis work "I Diagnose Situational Tourist of the Rural Parish Santiago of the Canton Loja", with the gathered information they were carried out surveys to people of the town to obtain the population's points of view as for the tourism. In the development of the Plan of Marketing, a fundamental part was the elaboration of the main FODA where was investigated the strengths, opportunities, weaknesses and threats, by means of the evaluation of the internal and external factors one could know which they are that they affect the tourist promotion of the Protective Forest of Sayo. In the proposal of the Plan of Marketing he/she thinks about four objectives that look for the solution of these factors that you/they are increasing the visit of the tourists by means of a plan of publicity, the same one that has a budget valued in $9845.80 dollars. Another of the objectives is to carry out a training plan for native guides and obtaining of license of tourist guides of the parish Santiago, same that counts with the support of the Ministry of Tourism; it is also sought to create center of tourist information, for the diffusion and information of the attractiveness of the parish Santiago, this he/she needed a budget of $8015,00 dollars and as last strategic objective it is to carry out a program of señalética implementation for the protective forest Sayo with a budget of $3170,00 dollars. The main results to those that you has arrived in this investigation were: that in the market study, it has been determined that the affluence of tourists in the parish Santiago is shown favorable, such so a potential demand has settled down per year for the project, what allows to foresee 7 that the business opportunity is attractive. The tourist promotion study, will be given to the national tourists and foreigners in the such routes as the Entrance to the park, the gulch Sayo, the sulfurous waters among other, being attractive places of more relevance, which possess diversity of natural resources. The promotion center will be the Protective Forest Sayo located in the Parish Santiago where it will be distributed in specific areas to diffuse the tourism.